The Anti-dyslipidemic Effects of Milled Root Bark Ethanolic Extract of Capparis erythrocarpus in Sprague-Dawley Rats: Implications for Obesity and Cardiovascular Diseases - P. Saka, K. E. Osafo, S. Antwi, O. N. K. Martey, O. Quasie, M. Antwi-Adjei, J. Asiedu-Larbi, N. K. Takyi, K. N Donkor, L. K. N. Okine (Journal of Applied Pharmaceutical Science, 2018)
Dyslipidaemia is a major risk factor of the onset of cardiovascular disease and obesity. Sirappac, the milled root bark of C. erythrocarpus has been reported to significantly reduce body weight and sizes of Sprague-Dawley rats with possible effects on the alteration of lipid metabolism. The present study was thus, aimed at determining the effects of sirappac on the body weight, food intake, serum lipid levels and blood pressures in rats. Male adult Sprague-Dawley rats were treated with sirappac at doses of 20, 100 and 200 mg/kg for a period of three months. Rats body weight and feed intake values were recorded daily. Serum triglycerides (TG), total cholesterol (TC), high density lipoprotein-cholesterol (HDLC), low density lipoprotein-cholesterol (LDLC) and leptin levels were determined monthly throughout the study period. At the end of the treatment period, there were significant (p
Keywords: Dyslipidaemia, cardiovascular disease, obesity, C. erythrocarpus.